Bell’s palsy: An Electro-acupuncture Approach - Su, Sreedaran; S, Veni; S, Geethanjali; S, Prashanth (Indian Journal of Integrative Medicine, 2025)
Peripheral facial palsy is a developing neurological disorder that directly affects the facial nerve and causes partial or complete paralysis of the face. The cause of disease is not clear but it commonly affects around 20 to 35 people per 100,000 each year. The present case report aims to determine the effect of acupuncture with electric stimulation to treat peripheral facial palsy with a few potent acupuncture points in shorter sessions. A 47-year-old female patient presented with facial asymmetry on the left side with slurred speech evaluated by the Sunny Brook Facial Grading system and short form-12 to assess quality of life. By taking pre-data, acupuncture with electric stimulation with 4Hz pulsed current was given for 15 consecutive sessions for each 20 minutes. days. After 15 days, post-data was obtained, which showed considerable changes in symptoms and data. This case report suggests that acupuncture with electrical stimulation is effective in treating Peripheral facial palsy.